Transfer Ribonucleic Acid Methylases During the Germination of Neurospora crassa - Wong, Rosemary S. L. (1971)
Transfer ribonucleic acid (tRNA) methylases were studied during the germination of spores in Neurospora crassa. The total methylase capacity and base specific tRNA methylase activities were determined in extracts from cells harvested at various stages of germination. Germinated conidia have a 65% higher methylase capacity than ungerminated conidia. Three predominant methylase activities were found in the extracts, and the relative amount of each activity was different at the various stages. Enzymes from vegetative cells catalyzed significant hypermethylation of tRNA from conidia, whereas conidial enzymes were much less active on tRNA from vegetative cells. The results indicate differences in the tRNA methylase content and tRNA species of conidia and vegetative cells.